THE ROLE OF YOUTH SPEECH IN THE PROCESS OF NATIONAL LANGUAGE CULTURE AND EDUCATION (World Bulletin of Social Sciences, 2026)
This article examines the role of youth speech in the development of national language culture and the educational process from theoretical and practical perspectives. In the context of globalization and digital transformation, significant changes are observed in the linguistic behavior of young people. The influence of social networks, deviations from literary language norms, code-switching practices, and the development of communicative competence are analyzed. The study is based on sociolinguistic survey data collected from 150 university students aged 18–25. The findings indicate that youth speech functions as an important indicator of national identity formation, moral values transmission, and socialization processes. Strengthening speech culture through educational and institutional mechanisms is essential for preserving linguistic heritage and ensuring cultural continuity.